PELAKSANAAN PEMBERIAN GANTI KERUGIAN DALAM PENGADAAN TANAH UNTUK PEMBANGUNAN JALAN TOL PEKANBARU-DUMAI (STUDI KECAMATAN KANDIS KABUPATEN SIAK) - ', Jefrizal; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Since the first land is very closely related to everyday human life and is a basic human needs of life. The amount of land that is not belanced with the large needs of the community to do the development for the implementation of various activities. The problem of compensation provided is not feasible or far exceeds the feasibility may cause riot. Therefore the grant of the compensation shall not cause the person to be deprived of his/her place of residence for not being able to purchase the land for the compensation. The government mechanism for compensation based on the value of the land, as per article 33 of law Nomor 12 of 2012 on land acuisiton for development for the public interest. The purpose of waiting this thesis, namely: First, the implementation of compensation in the procurement of land for the contruction of toll reoads Pekanbaru-Dumai (study Kandis Sub-district of Siak Regency), Secondly, the obstacle that cause the completion of compensation in the contruction of toll reoads Pekanbaru-Dumai (study Kandis Sub-district of Siak Regency).This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Kandis Sub-district of Siak Regency, while the population and sample were all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collection technique in research this is by interview and literature review.From the results of research problems there are two main things that can be concluded. First, the implementation in the form of compensation in the construction of Pekanbaru-Dumai toll road especially in Kandis District is not suitable as regulated in Law Number 2 Year 2012 About Land Procurement for Development for Public Interest. The government can only provide compensation in the form of money and adjusted to the budget of the government regardless of the condition of community land. Second, the obstacle to the completion of compensation in the construction of Pekanbaru-Dumai toll road is caused by several factors, namely: factors of society, factors of government, and factors of the company. Suggestion Writer, First, the government expected according to Law Number 12 of 2012 compensation should be fair and fair to the public. Secondly, the community must know the purpose of this development and if it is necessary to relinquish its land rights for the common good the community must be willing to voluntarily free the land.Keywords: Land - Indemnification - Procurement